Ochre Bathing of the Bearded Vulture: A Bio-Mimetic Model for Early Humans towards Smell Prevention and Health - Helmut Tributsch (Animals, 2016)
Since primordial times, vultures have been competing with man for animal carcasses. One of these vultures, the once widespread bearded vulture ( Gypaetus barbatus ), has the habit of bathing its polluted feathers and skin in red iron oxide - ochre - tainted water puddles. Why? Primitive man may have tried to find out and may have discovered its advantages. Red ochre, which has accompanied human rituals and everyday life for more than 100,000 years, is not just a simple red paint for decoration or a symbol for blood. As modern experiments demonstrate, it is active in sunlight producing aggressive chemical species. They can kill viruses and bacteria and convert smelly organic substances into volatile neutral carbon dioxide gas. In this way, ochre can in sunlight sterilize and clean the skin to provide health and comfort and make it scentless, a definitive advantage for nomadic meat hunters. This research thus also demonstrates a sanitary reason for the vulture’s habit of bathing in red ochre mud. Prehistoric people have therefore included ochre use into their rituals, especially into those in relation to birth and death. Significant ritual impulses during evolution of man may thus have developed bio-mimetically, inspired from the habits of a vulture. It is discussed how this health strategy could be developed to a modern standard helping to fight antibiotics-resistant bacteria in hospitals.